1998
DOI: 10.1126/science.280.5360.101
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Short-Range Repressors with Drosophila CtBP in the Embryo

Abstract: Human CtBP attenuates transcriptional activation and tumorigenesis mediated by the adenovirus E1A protein. The E1A sequence motif that interacts with CtBP, Pro-X-Asp-Leu-Ser-X-Lys (P-DLS-K), is present in the repression domains of two unrelated short-range repressors in Drosophila, Knirps and Snail, and is essential for the interaction of these proteins with Drosophila CtBP (dCtBP). A P-element-induced mutation in dCtBP exhibits gene-dosage interactions with a null mutation in knirps, which is consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
244
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(256 citation statements)
references
References 25 publications
11
244
0
1
Order By: Relevance
“…For example, transheterozygous knirps and CtBP embryos have disruptions in eve expression, suggesting that Knirps function is partially impaired, and a frameshift mutation in knirps encoding a protein lacking the CtBP binding motif is a strong hypomorph (Gerwin et al, 1994;Nibu et al, 1998a). Furthermore, a point mutation in the CtBP binding motif results in a protein that lacks the dominant phenotype of the wild-type protein when misexpressed in a pattern of eve stripe 2 (Nibu et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, transheterozygous knirps and CtBP embryos have disruptions in eve expression, suggesting that Knirps function is partially impaired, and a frameshift mutation in knirps encoding a protein lacking the CtBP binding motif is a strong hypomorph (Gerwin et al, 1994;Nibu et al, 1998a). Furthermore, a point mutation in the CtBP binding motif results in a protein that lacks the dominant phenotype of the wild-type protein when misexpressed in a pattern of eve stripe 2 (Nibu et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…The CtBP co-repressor is required for full activity of shortrange repressors such as Knirps, Krüppel, Giant and Snail that play important roles in patterning the blastoderm embryo (Nibu et al, 1998a;Nibu et al, 1998b). This evolutionarily conserved co-factor also interacts with a number of vertebrate transcriptional regulators, including the adenovirus E1A protein, Net, Ikaros, Zeb and, indirectly, the Retinoblastoma tumor suppressor protein (reviewed by Chinnadurai, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Gt and other segmental proteins have been characterized as shortrange repressors that interfere with the activity of cis-regulatory or promoter elements when bound up to 100 bp away (Nibu et al, 1998;Hewitt et al, 1999). It is thought that shortrange repressors might quench neighboring activators, inhibiting their access to the DNA or blocking their interaction with other components of the transcriptional machinery (Kulkarni and Arnosti, 2005).…”
Section: Discussion Gt Acts As a Morphogen For The Striped Pattern Rementioning
confidence: 99%
“…Indirect evidence has indicated that CtBP may modulate the metastatic potential of the adenoviral E1A protein (Boyd et al, 1993;Schaeper et al, 1995;Sollerbrant et al, 1996). This modulation activity of CtBP may be exerted through transcriptional regulation since the Drosophila homolog of CtBP has recently been shown to function as a short-range transcriptional repressor (Nibu et al, 1998;Poortinga et al, 1998). The direct associations of CtIP with CtBP and BRCA1 suggest that CtIP participates in some aspects of transcriptional regulation either in the E1A or BRCA1 pathway.…”
Section: Discussionmentioning
confidence: 99%